2011
DOI: 10.1016/j.jaapos.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Medical and surgical outcomes in childhood glaucoma: A population-based study

Abstract: Introduction To describe the clinical and surgical outcomes among patients under 20 years of age diagnosed with glaucoma in a defined population over a 40-year period. Methods The medical records of all patients (<20 years) diagnosed with glaucoma in Olmsted County, Minnesota, from January 1, 1965, through December 31, 2004, were retrospectively reviewed. Results Thirty children (45 eyes) were diagnosed with various forms of glaucoma during the 40-year study period. During a mean follow-up of 12.5 years (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…As expected, visual impairment accounts for the largest number of disabilities in patients with primary congenital glaucoma [ 12 13 ]. Many studies have reported visual prognosis, with 10% losing sight and about 50% having low vision [ 14 15 16 17 18 19 ].…”
Section: Discussionmentioning
confidence: 70%
“…As expected, visual impairment accounts for the largest number of disabilities in patients with primary congenital glaucoma [ 12 13 ]. Many studies have reported visual prognosis, with 10% losing sight and about 50% having low vision [ 14 15 16 17 18 19 ].…”
Section: Discussionmentioning
confidence: 70%
“…It remains an important cause of childhood blindness (3, 7, 8). Primary congenital glaucoma is a recognizable clinical problem in Saudi Arabia, absorbing a significant amount of clinical resources (9) with significant morbidity, leading to lifelong visual disability (10, 11). Some studies revealed that PCG appears in a more severe form in Saudi Arabia than in Western countries (12).…”
Section: Introductionmentioning
confidence: 99%
“…7,15,16 The present study was performed to evaluate genetic ancestry and its correlation with clinical data to assess variations in risk factors and disease prognosis.…”
mentioning
confidence: 99%